Pendekatan Deep Learning dalam Pembelajaran Pendidikan Agama Islam - Muhammad Nurul Ihsan Asmawi; Ahmad Luki Afifi; Purnomo (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
This study examines the application of the deep learning approach in Islamic Religious Education (PAI) learning, with a focus on analyzing its implementation in the educational environment. This approach aims to improve the effectiveness of learning through more interactive and in-depth methods. Thus, this study seeks to provide insight into how the deep learning approach can be integrated to enrich the PAI learning process. This study uses a qualitative approach with data collection techniques through library studies and literature reviews. This method aims to explore information and in-depth understanding from various written sources that are relevant to the research topic. This study suggests the need for intensive training for teachers to optimize the application of the deep learning approach in Islamic Religious Education (PAI) learning. It is hoped that these findings can be a reference in developing PAI learning activities that are more interactive, innovative, and relevant to students' lives. Thus, the learning process can be more interesting and effective and can shape the character and skills needed by students in the 21st century.